Gastroduodenal Bleeding and Perforation in Diabetic Patients with Metabolic Syndrome (The Results of a 15-Year Observation of City Residents with Intensive Urbanization) - Marat IMASHEV; Roman FURSOV; Alexandr FURSOV; Bagdat IMASHEVA; Roman FURSOV; Yerzhan KUSPAEV; Timofei KOVALENKO; Alishan ISMAILOV; Aigul ABDULDAYEVA; Irina VOLCHKOVA (Tehran University of Medical Sciences, 2019)
Background: The prevalence of bleeding and perforation against the diabetes mellitus, obesity and metabolic syndrome (MetS) is studied not sufficiently. Methods: The period of collecting the material was 15 years (2003-2017). The observation analysis was conducted for the patients at polyclinics observations, by the doctors of first-aid, in the surgical departments of the Astana City, Kazakhstan. The number of first-aid visits to patients, the medical cards of the patients with gastroduodenal perforation (GDP) and gastroduodenal bleeding (GDB) were analyzed. Results: The rate of annual growth of indices of overall morbidity Rgm=1.0%, obesity in combination with diabetes was Ro=1.7%; and morbidity with metabolic syndrome was Rm=3.1%. The diagnosis of GDP was revealed in 0.63 men with MetS for every 100000 urban people. The diagnosis of GDB was registered in 2.12 men for 100000 urban people. The index of the annual growth in patients with MetS had the tendency to the growth (Rms=3.1%). Conclusion: The high medical and social significance of diseases of the digestive system among the adult population in Kazakhstan is determined by the annual increase in the incidence rate and a clear decrease in the quality of life of such patients, which necessitates the search for scientifically based ways to improve medical care for this population.